The Psychodynamics of Gender and Gender Role.
DOI: 10.1037/10450-005
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious responses to "mommy and I are one": Does gender matter?

Abstract: A are dissimilar before puberty, but not after" (p. 185). van Dam's assertion was meant to convey a joking protest against poor readiness among psychoanalytic theorists in accommodating developmental hypotheses to social and cultural change. The quote serves well also to introduce the puzzling "now-you-see-it, nowyou-don't'' quality of gender-related effects in our own experi-These studies were supported by the Magnus Bergvall Foundation and by Grant F24/95 from the Swedish Research Council for the Humanities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…It may be relevant, however, that the present experiment was run by a male experimenter, whereas the former experiment was run by a female. Some observations across our various data‐sets can be interpreted as implying that the gender of the experimenter matters (Sohlberg & Jansson, 2002). If so, our switch from a female to a male experimenter may explain why we replicated the predicted interaction, but at an overall negative level of mood rather than at the mixed positive/negative level seen in the previous experiment.…”
Section: Discussionmentioning
confidence: 99%
“…It may be relevant, however, that the present experiment was run by a male experimenter, whereas the former experiment was run by a female. Some observations across our various data‐sets can be interpreted as implying that the gender of the experimenter matters (Sohlberg & Jansson, 2002). If so, our switch from a female to a male experimenter may explain why we replicated the predicted interaction, but at an overall negative level of mood rather than at the mixed positive/negative level seen in the previous experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Sohlberg and Jansson (2002) contended: "In our view, a hypothesis that participants in properly conducted M I 0 experiments respond to the syntaxdependent meaning in the entire five-word pharse is supported by at least as much evidence as the opposite possibility" (p. 173, Footnote 1). Weighing successful versus unsuccessful SPA outcomes is spurious.…”
Section: Sohlberg and Birgegard On Informationmentioning
confidence: 97%
“…Sohlberg and colleagues predicted mood level and, consequently, the quality of poststimulation behavior following M I 0 (e.g., Sohlberg, Samuelberg, Siden, & Thorn, 1998). Scores on a measure devised by Sohlberg and Jansson, similar to Silverman's differentiation-from-mother scale, were used to predict mood level (Sohlberg & Jansson, 2002). Participants rated themselves, then their mothers, on an adjective checklist.…”
Section: Sohlberg and Birgegard On Informationmentioning
confidence: 99%
“…Although suggestive only, data in one of their experiments were even consistent with effects lasting several months. The selection of these particular stimuli MIO and MIDIS was based on the well‐established effects of MIO (for a meta‐analysis see Hardaway, 1990; for a review see Weinberger & Hardaway, 1990; also see Sohlberg, Billinghurst & Nylén 1998; Sohlberg, Claesson & Birgegard, 2003; Sohlberg & Jansson, 2002). Participants were first seen individually in the laboratory and exposed to the stimuli, and ten days later they returned for a questionnaire session.…”
Section: Introductionmentioning
confidence: 99%
“…While all humans may be equipped to show sustained response to some subliminal stimulation, the concrete content of what is activated is likely to be somewhat distinct depending on other variables, for instance sex. Sohlberg and Jansson (2002) concluded that there were some differences between women and men in response to the MIO stimulus. That stimulus was shown to yield qualitatively similar effects to MIDIS in Experiment 2 of Sohlberg and Birgegard (2003), suggesting that sex‐specific results could occur with MIDIS also.…”
Section: Introductionmentioning
confidence: 99%